1998
DOI: 10.1109/83.650856
|View full text |Cite
|
Sign up to set email alerts
|

Optimal approximation of uniformly rotated images: relationship between Karhunen-Loeve expansion and discrete cosine transform

Abstract: Abstract-We will present in this correspondence that for uniformly rotated images, the optimal approximation of the images can be obtained by computing the basis vectors for the discrete cosine transform (DCT) of the original image in polar coordinates, and representing the images as linear combinations of the basis vectors.Index Terms-Discrete cosine transform, Karhunen-Loeve expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…As a word of caution, several authors including [9] and [10], mistakenly reported the formula for the eigenvectors proportional to ( )…”
Section: Eigenvalues and Eigenvectors Of Symmetric Circulantmentioning
confidence: 99%
See 1 more Smart Citation
“…As a word of caution, several authors including [9] and [10], mistakenly reported the formula for the eigenvectors proportional to ( )…”
Section: Eigenvalues and Eigenvectors Of Symmetric Circulantmentioning
confidence: 99%
“…For example, a SC matrix is used in physical applications [6] and image processing to describe the Karhunen-Loève type rotations of image templates [9] [11]. Generally, the SC matrix may be useful in modeling rotationinvariant systems in equilibrium.…”
Section: Applicationsmentioning
confidence: 99%
“…See Han and Vasconcelos (2010). The accuracy of the stereo matching is measured by the ratio of the number of correct matches to the total number of matches obtained using (23), as R(1) varies in I (1). Let this ratio be r esd (m, k 1 ).…”
Section: Stereo Matchingmentioning
confidence: 99%
“…In [71] it was already shown that the result of applying PCA to a set of rotated images has some remarkable effects: although there is only one changing source (the angle of rotation) multiple intensity sources are estimated from this data set. Moreover, the eigenvalues do not have the be estimated with an eigenvalue decomposition, they can also be found using Discrete Cosine Transform (DCT).…”
Section: Modeling Introductionmentioning
confidence: 99%
“…In [71] it was already shown that model errors can determine the characteristics of the eigenvalue plots: Uenohara and Kanade showed that the eigenvalues of a training set composed of rotated versions of one image can be determined using DCT as well as by doing an eigenvalue decomposition.…”
Section: Introductionmentioning
confidence: 99%